Cytologic evaluation of p16 staining in head and neck squamous cell carcinoma in CytoLyt versus formalin‐fixed material. Issue 12 (10th October 2019) - Buonocore, Darren J.; Fowle, Evan; Lin, Oscar; Xu, Bin; Katabi, Nora; Cohen, Jean‐Marc
Abstract : Background: The management of high‐risk human papillomavirus (HR‐HPV)–related oropharyngeal head and neck squamous cell carcinomas (HNSCCs) are distinct from HNSCC linked to smoking and alcohol use. HR‐HPV–positive HNSCC frequently presents as a cervical lymph node metastasis. Because fine‐needle aspiration (FNA) is often the initial diagnostic procedure, evaluating HR‐HPV status in cytology specimens is important. The overexpression of p16 is a surrogate for HR‐HPV; however, the evaluation of p16 in FNAs remains controversial. Methods: From September 2015 to December 2016, cytopathologists performed 25 FNAs of neck lymph nodes that were suspicious for HR‐HPV–positive HNSCC. Initial passes produced smears for on‐site evaluation and CytoLyt material. Additional passes were formalin‐fixed. A CytoLyt cell block (CCB) and a formalin‐fixed cell block (FFCB) were prepared, and p16 immunocytochemistry was performed. Results: In 24 of 25 cases, the FFCB had diffuse (≥70% of cells), strong nuclear/cytoplasmic p16 staining. In all 24 of these cases, HR‐HPV was detected by in situ hybridization. The corresponding CCB had weak‐to‐moderate p16 staining in <70% of cells (range, 5%‐60% of cells) in 17 cases, 4 had weak‐to‐moderate diffuse staining, and 4 were acellular. The percentage of p16‐positive cells was significantly higher with FFCB than with CCB (formalin: 94% ± 2%; CytoLyt, 38% ± 7%; 2‐tailed, paired Student t test; P < .001; Fisher exact test, P < .001). Conclusions: The fixative used had a drastic impact on p16 staining, which explained the staining variability reported in the literature. FFCBs show a diffuse staining pattern, which correlates with HR‐HPV status, whereas CCBs show a weaker and inconsistent staining pattern, which is more difficult to interpret. Abstract : In head and neck squamous cell carcinoma, HPV status is often evaluated by using p16 staining as a surrogate marker regardless of collection methods and fixation. In this study, CytoLyt fixation inhibits p16 immunoreactivity in fine‐needle aspiration material, whereas formalin does not.